Biopsy-resolved cryo-EM structures of amyloid fibrils provide molecular insights into AL amyloidosis - Yuxuan Yao; Qinyue Zhao; Shun Yao; Yamei Xu; Kaien Liu; Tianyi Cao; Bo Sun; Jingmin Zhou; Cong Liu; Dan Li (Proceedings of the National Academy of Sciences, 2026)
Systemic light chain amyloidosis (AL) is characterized by amyloid fibril deposition in multiple organs, often severely affecting cardiac function. In this study, we extracted amyloid fibrils directly from abdominal fat and cardiac tissue biopsies obtained from three AL patients. Using cryo-electron microscopy, we determined five distinct structures of light chain (LC) amyloid fibrils. Our results demonstrate that LC fibrils from different patients adopt unique structural conformations, highlighting patient-specific fibril variations. Conversely, LC fibrils extracted from different tissues within the same patient share highly similar overall fibril structures, yet exhibit localized conformational variations, potentially shaped by distinct environmental cofactors. This study emphasizes the combined roles of patient-specific protein sequences and tissue-specific microenvironments in defining LC fibril conformation. The determination of LC fibril structures directly from easily accessible abdominal fat biopsy provides critical molecular insights into AL amyloidosis pathology, facilitating the development of therapeutic strategies.